ANALISIS KINERJA KEUANGAN UNIT SIMPAN PINJAM PADA KOPERASI SERBA USAHA UPKD ARAU BINTANG JAYA KECAMATAN SUKARAJA KABUPATEN SELUMA - Misparleni Misparleni; Neri Susanti; Rinto Noviantoro (Universitas Prof.Hazairin,SH Bengkulu, 2019)
The objective of this research is to determine the financial performance of the savings and loan unit at Koperasi Serba Usaha UPKD Arau Bintang Jaya in Sukaraja Sub-District OF Seluma Regency The analytical method use was can analysis of financial performance from financial statements, namely the balance sheet and PHU( Calculation of Business Result). balance sheet and PHU (Calculation of Business Results). Using savings and loans assessment analysis based on the Deputy for Supervision of the cooperatives and small medium enterprises of the Republic of Indonesia Number 06 / Per / Dep.6 / IV / 2016 in 2015-2017. The average score of the financial performance evaluation of Koperasi Serba Usaha UPKD Arau Bintang Jaya in 2015 was 68.10 with a fairly healthy assesment. Koperasi Serba Usaha UPKD Arau Bintang Jaya in 2016 was 66.35 with a fairly healthy rating. The average score of Koperasi Serba Usaha UPKD Arau Bintang Jaya in 2017 was 66.60 with a fairly healthy assessment.